Seismic design of geosynthetic-reinforced earth retaining walls following a pseudo-static approach. Issue 1 (1st October 2022) - Gaudio, D; Masini, L; Rampello, S
Abstract: Geosynthetic-reinforced earth (GRE) retaining walls show a better performance than conventionally-designed walls during destructive earthquakes, due to their capability of redistributing seismic-induced deformations within the reinforced zone. In this paper, a recently-proposed method to design GRE walls is first recalled, where the wall is designed to trigger an internal plastic mechanism in the presence of strong earthquakes. Following a pseudo-static approach, the seismic coefficient k is therefore assumed equal to the internal seismic resistance of the wall k c int . The seismic coefficient is then calibrated against given seismic wall performance, expressed in terms of limit values of earthquake-induced displacements. Permanent displacements are evaluated through empirical relationships that were previously developed on the basis of a parametric integration of an updated Italian seismic database. Effectiveness of the proposed procedure is then demonstrated by assessing, through Finite Difference nonlinear dynamic analyses, the seismic performance of two walls, namely a GRE and a conventional gravity wall, characterised by the same seismic resistance but triggering an internal and external plastic mechanism, respectively. They are both subjected to a real strong motion, capable of activating a plastic mechanism. Results showed that lower permanent displacements are accumulated in the GRE wall where internal mechanisms are triggered.